Volumetric and transport properties of binary liquid mixtures with 1-ethyl-3-methylimidazolium ethyl sulfate as candidate solvents for regenerative flue gas desulfurization processes. (April 2018) - Živković, Emila M.; Živković, Nikola V.; Majstorović, Divna M.; Stanimirović, Andrej M.; Kijevčanin, Mirjana Lj.
Highlights: Potential solvents for flue gas desulfurization processes were investigated. Densities, viscosities and refractive indices of four binary mixtures were measured. Thermal conductivity of two binary solutions was determined. Excess and deviation functions were calculated. Modelling of viscosity and thermal conductivity was performed. Abstract: This paper presents novel data on density, viscosity and refractive index of four binary mixtures constituted of ionic liquid 1-ethyl-3-methylimidazolium ethyl sulfate and N-methyl-2-pyrrolidone/or 1-hexanol/or liquid polyethylene glycols with molar mass 200/or 400, in the temperature range from T  = 288.15 K to 333.15 K and at pressure of p  = .1 MPa. Thermal conductivity has been measured for mixtures of ionic liquid and polyethylene glycol 200/or polyethylene glycol 400 in the temperature range from T  = 303.15 to 323.15 K and at a pressure of p  = .1 MPa. All these solutions have the potential for application in regenerative flue gas desulfurization processes. From experimental values of densities, viscosities, thermal conductivities and refractive indices, excess molar volumes and deviations in viscosity, thermal conductivity and refractive index have been calculated and correlated with Redlich-Kister polynomial equation. The values of excess and deviation functions were used for analysis of molecular interactions present in the investigated solutions. In addition, modeling of transport properties, viscosity and thermal conductivity, was carried out and the obtained results were interpreted taking into account the applied approaches and models.